2014
DOI: 10.1556/avet.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of pseudorabies virus in domestic pigs and wild boars in Croatia

Abstract: Serological data imply that pseudorabies (Aujeszky's disease) is present in domestic pigs and wild boars in Croatia. Therefore, this study included testing of brain tissue samples collected from 200 domestic pigs and 105 wild boars originating from seventeen districts of Croatia. The presence of pseudorabies virus (PrV) DNA was confirmed in samples originating from six domestic pigs (3%) and one wild boar (0.95%). Positive samples were sequenced and analysed on the basis of a gC genome fragment. PrV strains ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…Similar findings were reported by Keros et al, [ 31 ]. The authors reported that genetically identical viral strains belonging to Clade A were circulating in Croatia in wild boar and domestic pigs, according to the gC sequences derived from six domestic pigs and one wild boar.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported by Keros et al, [ 31 ]. The authors reported that genetically identical viral strains belonging to Clade A were circulating in Croatia in wild boar and domestic pigs, according to the gC sequences derived from six domestic pigs and one wild boar.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that PRV strains can spill over from the wild boar population to the domestic pig population and vice versa. Such bidirectional transmissions have been experimentally demonstrated [31,32], and phylogenetic analyses have confirmed that strains related to wild boars can cluster with those related to domestic pigs [11,33,34]. This is indeed the case here, with two French strains isolated from hunting dogs belonging to I-A Group 1 clustering with strains isolated from domestic pigs in other countries.…”
Section: Discussionsupporting
confidence: 78%
“…The results of gC sequence comparison revealed high genetic similarity with previously derived strain from wild boars, but also domestic swine from Croatia (Keros and others 2014). …”
Section: Discussionmentioning
confidence: 58%
“…The results of all applied methods confirmed the presence of PrV in the brain tissue of both tested hunting dogs and defined it as the causative agent in both presented cases. Phylogenetic analysis revealed that both PrV strains derived from the brain tissue of infected dogs, clustered into a Clade A that comprises the majority of all characterised PrV strains along with PrV strains detected in domestic pigs and wild boars in Croatia (Keros and others 2014). PrV strains derived from dogs share 99.4 per cent and 99 per cent identities on nucleotide (nt) and amino acid (aa) level, respectively.…”
Section: Outcome and Follow‐upmentioning
confidence: 99%